Virtual Patriot Games: American Football in The Times of London, 1888–1910. Issue 11 (24th July 2017) - Dzikus, Lars; Dubinsky, Yoav
Abstract: This study examines the American football press coverage in the Times of London from 1888 to November 1910. The time span covers the paper's first mention of the game to the first game played in England. This period also coincides with increasing anxiety about the strength of the British Empire and unwanted American influences. During this time, athletic contests between the two nations turned into sites for the construction of national identities. Adapting the sport scholar Emma Poulton's concept of 'mediated patriot games', the author argues that the American football coverage of the Times of London could be considered 'virtual patriot games', as the absence of domestic American football teams did not allow for direct competition. Two related narrative elements. The stories in the Times framed gridiron football as the pastime of the 'other', including translating rules and comparing the merits of rugby and American football. The reports also focused on the American game's violence, confirming older traditions in British imaginations of America. Advancements in communication technologies, especially the telegraphic wire, were critical for the immediacy with which British readers consumed American sporting news. Contrary to current scholarship, British interpretations of American culture through gridiron football developed much earlier than the post-1970s information age.